Lousy big guys: Lepidophthirus macrorhini infesting seals from Antarctica - Leonardi, María Soledad (2017)
The present work represents a contribution to the ecology of a little known host parasite association, i.e. sucking lice and Antarctic seals. The information available regarding the health status of Antarctic seals is limited and little is known about the ecology and effect of parasites on these hosts. Particularly, data regarding Antarctic louse infestation are scarce. Therefore, the main goal of this study is to report the results of a survey of the louse infestation of Lepidophthirus macrorhini (Anoplura, Echinophthiriidae) on 26 elephant seals (Mirounga leonina) and on a Weddell seal (Leptonychotes weddelli) from eastern Antarctic Peninsula.